The Puffin Book of Stories for Eight-Year-Olds - Ed. Cooling, Wendy (Penguin Books Ltd, 1996)
This is a collection of stories that will keep children spellbound right up to the very last word.
Keywords: Juvenile literature-English language-Fiction